A non‐covalent functionalization of copper tetraphenylporphyrin/chemically reduced graphene oxide nanocomposite for the selective determination of dopamine. (16th November 2015) - Karuppiah, Chelladurai; Sakthinathan, Subramanian; Chen, Shen‐Ming; Manibalan, Kesavan; Chen, Sin‐Ming; Huang, Sheng‐Tung
Abstract : A non‐covalent functionalization based on a copper tetraphenylporphyrin/chemically reduced graphene oxide (Cu‐TPP/CRGO) nanocomposite is demonstrated for selective determination of dopamine (DA) in pharmaceutical and biological samples. A homogeneous electron‐rich environment can be created on the graphene surface by Cu‐TPP due to the π–π non‐covalent stacking interaction. The synthesized Cu‐TPP/CRGO nanocomposite was characterized using scanning electron microscopy NMR, ultraviolet–visible and electrochemical impedance spectroscopies. The electrocatalytic activity of DA was evaluated using cyclic voltammetry and differential pulse voltammetry. The oxidation peak current ( I pa ) of DA increased linearly with increasing concentration of DA in the range 2–200 μM. The detection limit was calculated as 0.76 μM with a high sensitivity of 2.46 μA μM −1 cm − 2 . The practicality of the proposed DA sensor was evaluated in DA hydrochloride injection, human urine and saliva, and showed satisfactory recovery results for the detection of DA. In addition, the Cu‐TPP/CRGO nanocomposite‐modified electrode showed excellent stability, repeatability and reproducibility towards the detection of DA. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A homogeneous electron‐rich environment generated via non‐covalent functionalization of copper tetraphenylporphyrin/chemically reduced graphene oxide (Cu‐TPP/CRGO) nanocomposite and it's specificity toward dopamine (DA) detection in pharmaceutical and biological samples.